Impact of Covid-19 on Mushroom Marketing in India: The Resilience of the Mushroom Market Amidst the Covid-19 Pandemic (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Mushroom is a micro food fungus, which is seen the naked eye, whose body is rounded topor, umbrella -shaped, it is eaten as a vegetable and other products. It is full of high nutritional andmedicinal properties, itcontain high protein, fiber, vitamin D, antioxidants and lowcarbohydrate, fats,minerals, and cholesterol free,itcalled the power of house of nutrition. Mushrooms are only vegetariansource of vitamin D. Covid is serious infections respiratory disease, which has devastated the human lifeof the whole and brought the economy down. Coronapandemic is the biggest challenging for the all overworld. Due to the lockdown in India, people of all classes had to face financial, health problems. Theglobal pandemic corona affected India‟s social, economic, political, educational, cultural, structure,physical and mental health as well as every outlook of life. In the initial days of the lockdown, there was asharp drop in mushrooms and mushrooms products,such as like pickle,jam, juice, bread, noodles,biscuits,consumption ranging from 50 to 80. Due to covid, the mushroom consumption, market size,major vendors, growth factors, sales size, market share, volume cost structure were impacted. But dueto the health benefits of mushrooms being full of medicinal properties, there was a positive effect on themushroom market due to the strong share of the retailer and the increase in consumption with thecooperation of the consumer.Coronavirus directly affects the immune system, mushroom have antivirus,antifungal, antibacterial, properties, which fight the corona virus and protects, the body from variousdiseases by increasing immunity. During covidperiod, due to the consuming of mushrooms in the diet byconscious consumerdemand increased in the market and some farmers tried to improves their incomeand economy health of the country by adopting mushroom cultivation. The worldwide lockdown affectedthe mushroom distribution channel structure. Due to the income of the farmers was affected but therewas a positive effect on the mushroom market. In agricultural countries like India mushroom cultivationand marketing self- employment,business, and economic development can be a miracle for a healthy life.